Revisiting Intensity Interferometry Using Picosecond Timescale Resolution - Camarata, Matthew A.; Horch, E. P. (Bulletin of the American Astronomical Society, 2011)
After the success of Hanbury Brown, Davis, and their collaborators in measuring all stellar diameters resolvable by the 166-m interferometer at Narrabri nearly four decades ago, research into optical intensity interferometry was largely discontinued. Signal-to-noise ratios and timing resolutions limited the technique to relatively bright stars over a narrow bandwidth. Modern photon-correlation electronics, however, may help to revive the technique, allowing for increased temporal resolution and longer baselines. In this paper, the PicoHarp 300 Time-Correlated Single Photon Counting System is characterized in order to demonstrate its ability to perform interferometric measurements. Time correlations of coherent and incoherent source apertures are measured and their autocorrelations compared with theory. The speed of light is also directly measured using the shift in temporal correlation between offset detectors. Finally, the possibility of two independent systems, linked between two large-aperture telescopes, is discussed with the goal of determining whether longer baselines can be achieved.
Keywords: dept.phy; ⛔ No DOI found

Speckle Imaging at Gemini and the DCT - Horch, E. P.; Löbb, J.; Howell, S. B.; van Altena, W. F.; Henry, T. J.; van Belle, G. T. (Revista Mexicana de Astronomía y Astrofísica, 2018)
A program of speckle observations at Lowell Observatory's Discovery Channel Telescope (DCT) and the Gemini North and South Telescopes will be described. It has featured the Differential Speckle Survey Instrument (DSSI), built at Southern Connecticut State University in 2008. DSSI is a dual-port system that records speckle images in two colors simultaneously and produces diffraction limited images to V∼ 16.5 mag at Gemini and V∼ 14.5 mag at the DCT. Of the several science projects that are being pursued at these telescopes, three will be highlighted here. The first is high-resolution follow-up observations for Kepler and K2 exoplanet missions, the second is a study of metal-poor spectroscopic binaries in an attempt to resolve these systems and determine their visual orbits en route to making mass determinations, and the third is a systematic survey of nearby late-type dwarfs, where the multiplicity fraction will be directly measured and compared to that of G dwarfs. The current status of these projects is discussed and some representative results are given.
Keywords: binaries: visual; dept.phy; techniques: high angular resolution; techniques: interferometric; techniques: photometric; ⛔ No DOI found

The Kepler follow-up observation program. I. a catalog of companions to Kepler stars from high-resolution imaging - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; van Belle, G. T.; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We present results from high-resolution, optical to near-IR imaging of host stars of Kepler Objects of Interest (KOIs), identified in the original Kepler field. Part of the data were obtained under the Kepler imaging follow-up observation program over six years (2009-2015). Almost 90% of stars that are hosts to planet candidates or confirmed planets were observed. We combine measurements of companions to KOI host stars from different bands to create a comprehensive catalog of projected separations, position angles, and magnitude differences for all detected companion stars (some of which may not be bound). Our compilation includes 2297 companions around 1903 primary stars. From high-resolution imaging, we find that ∼10% (∼30%) of the observed stars have at least one companion detected within 1″ (4″). The true fraction of systems with close (≲4″) companions is larger than the observed one due to the limited sensitivities of the imaging data. We derive correction factors for planet radii caused by the dilution of the transit depth: assuming that planets orbit the primary stars or the brightest companion stars, the average correction factors are 1.06 and 3.09, respectively. The true effect of transit dilution lies in between these two cases and varies with each system. Applying these factors to planet radii decreases the number of KOI planets with radii smaller than 2 R⊕ by ∼2%-23% and thus affects planet occurrence rates. This effect will also be important for the yield of small planets from future transit missions such as TESS. © 2017. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; catalogs; dept.phy; peer-reviewed; planets and satellites: detection; surveys; techniques: high angular resolution; techniques: photometric

Erratum: “The Kepler Follow-up Observation Program. I. A Catalog of Companions to Kepler Stars from High-resolution Imaging” (2017, AJ, 153, 71) - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; Belle, G. T. van; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We have added references to Tables 3 and 8 (last column in each table). Below is a sample of both tables; the full tables are available in machine-readable form.
Keywords: dept.phy

HAT-P-67b: An extremely low density Saturn transiting an F-subgiant confirmed via doppler tomography - Zhou, G.; Bakos, G. Á.; Hartman, J. D.; Latham, D. W.; Torres, G.; Bhatti, W.; Penev, K.; Buchhave, L.; Kovács, G.; Bieryla, A.; Quinn, S.; Isaacson, H.; et al. (The Astronomical Journal, 2017)
We report the discovery of HAT-P-67b, which is a hot-Saturn transiting a rapidly rotating F-subgiant. HAT-P-67b has a radius of Rp=2.085 -0.071 +0.096 RJ, and orbites a M∗ = 1.642-0.072 +0.155 M, R∗ = 2.546-0.099 +0.0084 R host star in a ∼4.81 day period orbit. We place an upper limit on the mass of the planet via radial velocity measurements to be Mp < 0.59 MJ, and a lower limit of >0.056 MJ by limitations on Roche lobe overflow. Despite being a subgiant, the host star still exhibits relatively rapid rotation, with a projected rotational velocity of v sin I∗ = 35.8 ±1.1 km s-1, which makes it difficult to precisely determine the mass of the planet using radial velocities. We validated HAT-P-67b via two Doppler tomographic detections of the planetary transit, which eliminate potential eclipsing binary blend scenarios. The Doppler tomographic observations also confirm that HAT-P-67b has an orbit that is aligned to within 12, in projection, with the spin of its host star. HAT-P-67b receives strong UV irradiation and is among one of the lowest density planets known, which makes it a good candidate for future UV transit observations in the search for an extended hydrogen exosphere. © 2017. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HAT-P-67); techniques: photometric; techniques: spectroscopic

A hot terrestrial planet orbiting the bright M dwarf L 168-9 unveiled by TESS - Astudillo-Defru, N.; Cloutier, R.; Wang, S. X.; Teske, J.; Brahm, R.; Hellier, C.; Ricker, G.; Vand erspek, R.; Latham, D.; Seager, S.; Winn, J. N.; Jenkins, J. M.; et al. (Astronomy & Astrophysics, 2020)
We report the detection of a transiting super-Earth-sized planet (R = 1.39 ± 0.09 R⊕ ) in a 1.4-day orbit around L 168-9 (TOI-134), a bright M1V dwarf (V = 11, K = 7.1) located at 25.15 ± 0.02 pc. The host star was observed in the first sector of the Transiting Exoplanet Survey Satellite (TESS) mission. For confirmation and planet mass measurement purposes, this was followed up with ground-based photometry, seeing-limited and high-resolution imaging, and precise radial velocity (PRV) observations using the HARPS and Magellan/PFS spectrographs. By combining the TESS data and PRV observations, we find the mass of L 168-9 b to be 4.60 ± 0.56 M⊕ and thus the bulk density to be 1.74-0.33+0.44 times higher than that of the Earth. The orbital eccentricity is smaller than 0.21 (95% confidence). This planet is a level one candidate for the TESS mission's scientific objective of measuring the masses of 50 small planets, and it is one of the most observationally accessible terrestrial planets for future atmospheric characterization. © ESO 2020.
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Solar and Stellar Astrophysics; Atmospheric characterization; Earth (planet); High-resolution imaging; Mass measurements; Orbital eccentricity; Orbits; Planetary systems; Planets; Radial velocity; Scientific objectives; Seeing limited; Stars: individual: L 168-9; Stars: late-type; Techniques: photometric; Techniques: radial velocities; Terrestrial planets; dept.phy; peer-reviewed; planetary systems; stars: individual: L 168-9; stars: late-type; techniques: photometric; techniques: radial velocities